2012
DOI: 10.1371/journal.pone.0034490
|View full text |Cite|
|
Sign up to set email alerts
|

HTLV-1 Tax Mediated Downregulation of miRNAs Associated with Chromatin Remodeling Factors in T Cells with Stably Integrated Viral Promoter

Abstract: RNA interference (RNAi) is a natural cellular mechanism to silence gene expression and is predominantly mediated by microRNAs (miRNAs) that target messenger RNA. Viruses can manipulate the cellular processes necessary for their replication by targeting the host RNAi machinery. This study explores the effect of human T-cell leukemia virus type 1 (HTLV-1) transactivating protein Tax on the RNAi pathway in the context of a chromosomally integrated viral long terminal repeat (LTR) using a CD4 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 87 publications
0
42
0
2
Order By: Relevance
“…For example, miR181 modulates the T-cell antigen receptor sensitivity (44); miR150 regulates the transcription factor c-Myb13 and miR155 affects the differentiation of CD4 þ T lymphocytes into T helper type I (Th1) cells, regulatory T-cell development (45,46), and the promotion of T-cell-dependent tissue inflammation (46). HTLV-1 was previously shown to modify the pattern of miRNA expression in cell lines and ATLL samples (30)(31)(32)(33)(47)(48)(49)(50). Our results here add to these findings, as the miRNA expression profile of nonimmortalized infected T cells derived from carriers without malignancies was significantly distinct from that of uninfected cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, miR181 modulates the T-cell antigen receptor sensitivity (44); miR150 regulates the transcription factor c-Myb13 and miR155 affects the differentiation of CD4 þ T lymphocytes into T helper type I (Th1) cells, regulatory T-cell development (45,46), and the promotion of T-cell-dependent tissue inflammation (46). HTLV-1 was previously shown to modify the pattern of miRNA expression in cell lines and ATLL samples (30)(31)(32)(33)(47)(48)(49)(50). Our results here add to these findings, as the miRNA expression profile of nonimmortalized infected T cells derived from carriers without malignancies was significantly distinct from that of uninfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…By targeting Drosha to the proteasome, Tax influences global miRNA biogenesis (49). Furthermore, Tax activates the transcription of miR130b (33) and miR146a (32), and downregulates miR149 and miR873, which both directly target the chromatin-remodeling factors p300 and p/CAF that are known to play a critical role in HTLV-1 pathogenesis (47). Nonimmortalized HTLV-1-positive clones express a wide range of Tax RNA levels, likely modifying numerous cellular pathways (5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Purity of the cells was confirmed by flow cytometry, and 3 ϫ 10 5 myeloid dendritic cells were cultured in 0.5 ml of AIM-V medium (Invitrogen) in a 24-well plate and either left untreated or treated with exosomes from C81, CEM, and ED(Ϫ) cells (5 g of total protein) for 48 h. Cell-free Tax was also included at (50 nM) as per previously published studies (56, 66 -68). Culture supernatants from triplicate sample sets were used to measure the concentration (pg/ml) of a panel of 12 cytokines (IL-2, IL-4, IL-5, IL-6, IL-10, IL-12, IL-13, IL-17A, IFN-␥, TNF-␣, G-CSF, and TGF-␤1) using a human Th1/Th2/ Th17 cytokine multianalyte ELISArray according to the manufacturer's protocol (SABiosciences, Frederick, MD) and as described (69).…”
Section: Methodsmentioning
confidence: 99%
“…There are many other patterns involving virus-host interactions that need to be further investigated. For example, human miRNAs can directly target viral genomes for defense (Lecellier et al, 2005), and viral proteins were also found to regulate expression of human miRNAs that targeted host chromatin remodeling proteins (Rahman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%